Análise comparativa da força no limite de escoamento entre um implante de peça única e os de junção hexagonal externa de diâmetros regular e estreito - Mundim, Arnaldo Reis (2008)
Osseointegrated implants have now been proved to be feasible. However, several factors still remain to be explained, particularly because of the large number of manufacturers and models. Although incidence is low, implant fractures are a clinical reality, and therefore researches are conducted in an endeavor to reduce their number. Objective: To test the hypothesis that the reduction in implant diameter reduces the maximum force required to attain the implant yield limit even when it is made in one piece. Materials and Methods: To test this hypothesis, three implant configurations (SIN) (n=10): HER, external hexagonal junction and regular diameter (3.75mm); HEE, external hexagonal junction and narrow diameter (3.25mm) and UNI, narrow one-piece (2.35mm) were tested. The maximum force at yield limit (N) for the implants was evaluated by means of the flexion test, with force applied perpendicular to the long axis of the implant, at the speed of 0.5 mm/min, in a mechanical test machine. The data were assed by means of the analysis of variance (ANOVA) and Tukey B tests for parametric groups (P<0.05). Results: Statistically significant differences were found between UNI and HER and HEE, and there were no statistically significant differences between the latter two. Conclusions: The UNI group presented statistically lower maximum resistance at the yield limit than the groups HEE and HER.